2021
DOI: 10.4317/jced.58051
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of traumatic injuries in deciduous dentition and associated risk factors in a Spanish children population

Abstract: Background The frequency of traumatic dental injuries (TDI) in primary dentition and those agents that favor them present a great variability. Therefore, the objective of this study was to determine the prevalence of TDI in a population of Spanish preschoolers in temporary dentition and identify the factors associated with these injuries. Material and Methods An epidemiological observational prevalence study was carried out. A total of 343 children aged between 3 and 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In some studies, males are the most affected; in others, it is women. On the other hand, in some studies, large percentage differences between men and women affected by trauma are observed, while in others, the differences are minimal [16,[21][22][23][24][25][26]28,[33][34][35][36][37][38]. Apparently, multiple aspects could influence the behavior of this variable, which are poorly addressed in the literature concerning deciduous dentition.…”
Section: Tdi In Deciduous Dentition and Its Relationship With The Gen...mentioning
confidence: 99%
“…In some studies, males are the most affected; in others, it is women. On the other hand, in some studies, large percentage differences between men and women affected by trauma are observed, while in others, the differences are minimal [16,[21][22][23][24][25][26]28,[33][34][35][36][37][38]. Apparently, multiple aspects could influence the behavior of this variable, which are poorly addressed in the literature concerning deciduous dentition.…”
Section: Tdi In Deciduous Dentition and Its Relationship With The Gen...mentioning
confidence: 99%